Analysis of Service and Safety of Goods Delivery on Consumer Interest in Grab Express Jakarta 2023 Sameday Delivery - Roswan Kasim; Ika Utami Yulihapsari; Muammar Farhan Falahi; Fikri Ikhwansyah (Jurnal Ekonomi Manajemen Sistem Informasi, 2025)
Grab Express service is an application that provides online goods delivery services in the community to provide convenience and guarantee the safety and speed of delivery of goods. The purpose of this study was to determine and analyze whether service and safety of goods affect future consumer interest in using the Grab Express service, especially for users in the city of Jakarta. This study uses a quantitative method, determining the sample size in this study using the Lemeshow formula because the population size is unknown. The number of samples used amounted to 100 from the calculation with the Lemeshow formula. Data was collected by distributing questionnaires made with Google forms that have been distributed online, which are users of the Grab Express service in Jakarta City. The results of this study indicate that there is a significant influence between service and safety of goods on consumer interest in using the Same day Grab Express delivery service.